On Dracograllus miguelitus sp. nov. (Nematoda: Draconematidae) from an inactive structure: insights into its taxonomy, biodiversity and ecology at hydrothermal vents - William Johnson da Silva; Daniela Zeppilli; Valentin Foulon; Pierre-Antoine Dessandier; Marjolaine Matabos; Jozee Sarrazin (PeerJ)
Background Hydrothermal vent fields are habitats to a diverse array of benthic organisms, including several nematode species, which represent a significant portion of the biodiversity in these environments. Despite their ecological importance, most research on hydrothermal vents has focused on macro-invertebrates. As a result, vent nematode biodiversity remains largely unexplored, especially in peripheral and inactive structures, underscoring the need for further investigation. A sampling program conducted in 2017 and 2018 along a gradient of venting activity led to the collection of a number of Draconematidae species in various habitats. In this article, we introduce Dracograllus miguelitus sp. nov., the first species of the genus described at a hydrothermal vent field, sampled from a visually inactive sulphide structure. Methods The samples were collected at the Lucky Strike vent field, on the Mid-Atlantic Ridge, using the suction sampler of the Remotely Operated Vehicle Victor6000. Specimens were retrieved from an edifice covered by a black layer of manganese oxy-hydroxides, with no local visible hydrothermal activity, at a depth of 1.639 m. Samples were sieved on a 32 µm mesh onboard, sorted and, for nematodes, identified to species level back in the lab. Fluorescent images were obtained using the ApoTome Fluorescence Microscope Module, and 3D observations were possible through the depth change method. Results We established D. miguelitus sp. nov. as a new species based on the combination of the following characters: four cephalic adhesive tubes (CATs), an elongated loop-shaped amphid with varying branch sizes between males and females, and a circular amphid in juveniles. Additionally, females display a minute setae emerging from the vulvar aperture. In males, the posterior adhesive tubes (PATs) are arranged in four longitudinal rows: two sublateral rows, each containing 10–12 PATs, and two subventral rows, consisting of 10 PATs in each. In females, sublateral and subventral rows with 13 PATs each. So far, D. miguelitus sp. nov. is the first species of the genus to be described from a hydrothermal environment and the deepest one. Beyond the formal description of this new species, we provide ecological and taxonomic backgrounds on Draconematidae at hydrothermal vents, with insights into the genus distribution, biogeography, and nomenclatural issues. Conclusion This discovery contributes to the knowledge of Draconematidae biodiversity, and highlights the importance to investigate nematode communities at species-level, data that is often missing at vent studies. Additionally, it underscores the significance of preserving inactive hydrothermal habitats, which are threatened by deep-sea mining activities.